Pointer instrument image recognition system for veterinary drug production based on RFID and deep learning. Issue 3 (October 2020) - Qiu, Qin; Cao, Shanshan; Wu, Jianzhai; Kong, Fantao; Sun, Wei
Abstract: Based on RFID technology, the tag data can be read and identified dynamically, real-time, contactless, long-distance and batch, and the image information of pointer instrument can be collected. Using Faster-RCNN to detect and locate the dial area, and combining with Le Net-5 method to identify the dial number, the system has the advantages of fast reading, high accuracy, strong adaptability and intelligent management. It provides a solution for the automatic recognition and reading of pointer instrument in the complex environment of veterinary medicine production workshop.